Listado de especies de la familia Orchidaceae para el estado Sucre, Venezuela - Leopardi, Carlos; Cumana, Luis (Lankesteriana: International Journal on Orchidology, 2008)
The family Orchidaceae is one of the most widespread groups of Magnoliophyta, they occur in a broad range of habitats, from the terrestrial habit to the treetops (epiphytes). Historically, this family had received a great deal of attention because of the beauty of the flowers of some species, which has lead to study its distribution; as a consequence, lists of species have been published for various places of America and the world. In Venezuela, except for treatments, of the family on a general level, there are few studies of local areas, and very little on the coastal cordillera; for that reason, we offer an updated list of the species of Orchidaceae so far know in the flora of Sucre state. To achieve this, the herbaria VEN and IRBR were studied during 2006- 2007, and the on-line database of herbaria K, MO, AMES, NY and F were consulted. Field exploration was undertaken in 14 localities in Sucre state, divided between the Peninsulas of Araya and Paria, around of Cumaná and the Macizo del Turimiquire. As results, we present a list of 121 species of 63 genera. The most important are: Epidendrum L. (16 spp.), Habenaria Willd. (8 spp.), Pleurothallis R. Br. s. l. (7 spp.), Maxillaria Ruiz & Pav. s. str. (4 spp.) y Scaphyglottis Poepp. & Endl. (4 spp.). Additionally, 12 species were mentioned in the literature, of which six have data (collector and collection number). Of the total of the species know from Sucre state, 15 was mentioned in the Red Book of the Venenezuelan flora, two of these are in critic danger (Cattleya gaskelliana Rchb. f. y Psychopsis papilio (Lindl.) H.G. Jones), one in danger, two vulnerable, the rest are in the category minor risk.